2016
DOI: 10.1017/s0033291716002002
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of focal psychodynamic therapy and enhanced cognitive–behavioural therapy in out-patients with anorexia nervosa

Abstract: Background. Anorexia nervosa (AN) is a serious illness leading to substantial morbidity and mortality. The treatment of AN very often is protracted; repeated hospitalizations and lost productivity generate substantial economic costs in the health care system. Therefore, this study aimed to determine the differential cost-effectiveness of out-patient focal psychodynamic psychotherapy (FPT), enhanced cognitive-behavioural therapy (CBT-E), and optimized treatment as usual (TAU-O) in the treatment of adult women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…The finding that CBT-E for adult patients with all types of eating disorders and a BMI >17.5 is superior to TAU from a costeffectiveness perspective is, to our knowledge, new. It is in contrast with the outpatient anorexia nervosa study of Egger, Wild, and Zipfel (2016), which found the probability of CBT-E being cost-effective compared to TAU was <90% for all WTPs.…”
Section: Discussioncontrasting
confidence: 75%
“…The finding that CBT-E for adult patients with all types of eating disorders and a BMI >17.5 is superior to TAU from a costeffectiveness perspective is, to our knowledge, new. It is in contrast with the outpatient anorexia nervosa study of Egger, Wild, and Zipfel (2016), which found the probability of CBT-E being cost-effective compared to TAU was <90% for all WTPs.…”
Section: Discussioncontrasting
confidence: 75%
“…Estimates for the sum cost of GSH intervention ($1,365.80) and prevention intervention ($505.86) were applied from the previous calculations. For individuals with anorexia nervosa, we used the cost from Egger and colleagues of $4,109.56 (converted to 2016 US dollars from €2,494) for delivering in‐person enhanced cognitive behavioral therapy (Egger et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Country or healthcare system practice guidelines may also impact the types of care utilized for treating anorexia nervosa; for example, in Germany, inpatient treatment is recommended initially as treatment for anorexia nervosa (Herpertz et al, ). Indeed, our model is limited in that we do not estimate the costs associated with higher levels of care for anorexia nervosa or other EDs (e.g., hospitalization, which bears high costs), medical expenditures that can result from EDs, or indirect costs associated with lost productivity, all of which increase total costs (Egger et al, ; Stuhldreher et al, ), meaning our calculation is an underestimate. We also do not account for the cost savings of avoiding excess medical utilization through prevention and early intervention associated with the stepped care model.…”
Section: Discussionmentioning
confidence: 99%
“…Byford et al () used the Morgan‐Russell Average Outcome Scale score as a primary outcome and found that specialized outpatient treatment for adolescents with AN (not limited to <3 years duration) including individual cognitive behavioural therapy (CBT) and parental counselling was more effective and less costly than inpatient treatment and TAU. Similarly, Egger et al () showed that outpatient psychotherapies for adults with AN, including focal psychodynamic therapy and enhanced CBT, were found to be less costly than optimized TAU in all outcomes examined (i.e., recovery, quality‐adjusted life years, BMI) from a societal economic perspective. It is noteworthy that both of these studies were economic evaluations conducted alongside clinical trials and that while the results supported the cost‐effectiveness of the active interventions, the differences between groups on both costs and outcomes were not statistically significant.…”
Section: Discussionmentioning
confidence: 96%